Congenital malformations in Assam - Dutta Hemonta; Bhattacharyya N; Sarma J; Kusre Giriraj (Wolters Kluwer Medknow Publications, 2010)
Aim : To determine the annual incidence of congenital malformations in Assam and to analyze the data. Materials and Methods : Data regarding babies born with congenital malformations in the state of Assam during the year 2006 were obtained through questionnaires and analyzed. The results were compared with similar Indian data. Results : The overall incidence of congenital malformation was 0.08%. This was considerably lower than similar published data from other states. Five hundred and eleven babies were born with congenital malformations, with 421 (82.4%) having major malformations. Males were affected more than females, 334 (65.4%) vs. 177 (34.6%). The gastrointestinal and genitourinary systems accounted for 26% and 25.8%, respectively. Malformation involving the central nervous system was more common in certain ethnic groups. Conclusions : The incidence of malformations in certain systems was at variance with the data from other states.